2014
DOI: 10.1186/preaccept-1588328929121802
|View full text |Cite
|
Sign up to set email alerts
|

Identifying USPs regulating immune signals in

Abstract: Background: Rapid activation of innate immune defences upon microbial infection depends on the evolutionary conserved NF-κB dependent signals which deregulation is frequently associated with chronic inflammation and oncogenesis. These signals are tightly regulated by the linkage of different kinds of ubiquitin moieties on proteins that modify either their activity or their stability. To investigate how ubiquitin specific proteases (USPs) orchestrate immune signal regulation, we created and screened a focused R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…A hundred DUBs have been identified in the human genome [ 15 , 16 ] and the Drosophila genome contains 41 DUB encoding genes, 34 of which having at least one human orthologue [ 17 ]. Genetic screens identified crucial DUBs involved in the regulation of apoptosis [ 18 ], of the Notch pathway [ 19 ] and of the innate immune response [ 20 ]. DUBs are categorized in five sub-families according to the structure of their catalytic domain: Ubiquitin C-terminal Hydrolases (UCH), Ubiquitin-Specific Proteases (USP), Machado-Joseph Disease Proteases (MJD), Otubain proteases (OTU) and JAB1/MPN/Mov34 Metalloenzymes (JAMM).…”
Section: Introductionmentioning
confidence: 99%
“…A hundred DUBs have been identified in the human genome [ 15 , 16 ] and the Drosophila genome contains 41 DUB encoding genes, 34 of which having at least one human orthologue [ 17 ]. Genetic screens identified crucial DUBs involved in the regulation of apoptosis [ 18 ], of the Notch pathway [ 19 ] and of the innate immune response [ 20 ]. DUBs are categorized in five sub-families according to the structure of their catalytic domain: Ubiquitin C-terminal Hydrolases (UCH), Ubiquitin-Specific Proteases (USP), Machado-Joseph Disease Proteases (MJD), Otubain proteases (OTU) and JAB1/MPN/Mov34 Metalloenzymes (JAMM).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a minority of them have been functionally characterized. The USPs are the biggest subfamily with more than 50 members 33 , with some of them known to regulate antiviral immune responses 28 , 34 , 35 . Previous studies have indicated that EV71 infection induces the up-regulation of USP19, which negatively regulates the antiviral type I interferon signalling by removing K-63 polyubiquitin chains from TRAF3 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The identified mutation in UPS36 gene is p.Arg631Gly. This gene is a known member of the ubiquitin specific protease family that regulates the immune signaling pathway [ 28 ]. The p.Arg338Cys mutation in SPN was also identified in our patients, and the influence of this gene can affect cellular defense responses and the regulation of the tumor necrosis factor (TNF) pathway [ 29 ].…”
Section: Discussionmentioning
confidence: 99%